Rekonstruksi Maqâshid al-Syarî`ah dalam Pengembangan Metodologi Hukum Islam (Kajian Eksploratif Pemikiran Jasser Auda) - Yaqin, Ainol (Madania: Jurnal Kajian Keislaman, 2018)
Abstract: The Reconstruction of Maqâshid al-Syarî`ah in Development of Islamic Law Methodology (Explorative Study of Jasser Auda’s Thoughts). Every Islamic law prescribed should be tucked with shariah objectives (maqâshid al-syarî`ah), which is expedient in the sense of broad sense that must be preserved or harm that should be rejected. Maqâshid al-syarî`ah is the result of the understanding, thought and cognition of scholars, both classical and contemporary scholars towards some syara’ (Islamic law) so that it is not patent, stagnant and permanent. Jasser Auda endeavors to rearrange, reconstruct and integrate maqâshid al-syarî`ah with all theories of Islamic legal methodology in order to respond to the complexity of the problems that engage Muslims. He conceptualized system theory to correct, analyze and rethink the methodology of Islamic law by making maqâshid al-syarî`ah its main base. This noble ijtihad is projected to present Islamic law with justice, equity, freedom, tolerance, compassion, civilization, brotherhood, human rights, humanity and environmental stewardship so that it can improve and build the main human resources of Islam in order to build a bright and advanced world civilization.